The Experience of Deconversion Among Polish Catholic Adolescents: A Mixed-Methods Investigation - Grupa, Michał (Journal of religion and health, 2025)
This study aimed to address a gap in the literature concerning the emotional dynamics of deconversion among adolescents, specifically focusing on the relationship between deconversion, anxiety, and the prior centrality of religion. Using a mixed-methods approach, the study combined qualitative research to uncover the lived experiences of Polish Catholic adolescents who have undergone deconversion, with a longitudinal quantitative design to examine changes in anxiety over time in relation to the initial centrality of religion. In Study 1, five adolescents (aged 15-18; M = 16.4, SD = 1.14) participated in in-depth, semi-structured interviews, which were analyzed using thematic analysis. Three main themes were generated from the data: Confronting Turmoil at the Beginning, Mourning the Loss of Foundational Beliefs, and Progressing toward Adaptation. In Study 2, 268 adolescents (aged 13-16 at Time 1) participated in a longitudinal quantitative study consisting of three measurement points, which utilized a linear mixed model (LMM) to investigate the relationships between anxiety, deconversion, time, and the centrality of religion. The results indicated that the link between deconversion and anxiety was strongest initially and decreased over time, particularly for adolescents who had previously placed high importance on religion. The findings highlight the emotional dynamics of adolescent deconversion and suggest that the prior centrality of religion plays a significant role in shaping the emotional impact of this process.